End of assignment report - Bárcena, Alicia (United Nations, ECLAC, 2022)
This document contains a report on the term in office of Alicia Bárcena as Executive Secretary of ECLAC (2008–2022), by area of work of the Commission.
11362/47840
Keywords: Graue Literatur; Amtliche Publikation; 2030 Agenda for Sustainable Development; inclusive development; inequality; international cooperation; public policies; sustainable development; international trade; ECLAC; activities; economic development; social development; gender equality; equality; social policy; CEPAL; ACTIVIDADES; AGENDA 2030 PARA EL DESARROLLO SOSTENIBLE; DESARROLLO ECONOMICO; DESARROLLO SOCIAL; DESARROLLO SOSTENIBLE; IGUALDAD DE GENERO; IGUALDAD; POLITICA SOCIAL; COOPERACION INTERNACIONAL; ACTIVITIES; 2030 AGENDA FOR SUSTAINABLE DEVELOPMENT; ECONOMIC DEVELOPMENT; SOCIAL DEVELOPMENT; SUSTAINABLE DEVELOPMENT; GENDER EQUALITY; EQUALITY; SOCIAL POLICY; INTERNATIONAL COOPERATION